Encapsulation of Lactobacillus rhamnosus GG in microparticles: Influence of casein to whey protein ratio on bacterial survival during digestion - Burgain, J.; Gaiani, C.; Cailliez-Grimal, C.; Jeandel, C.; Scher, J. (Innovative food science & emerging technologies, 2013)
Encapsulation of Lactobacillus rhamnosus GG in various microparticles made of only milk proteins (casein, native whey and/or denatured whey proteins) was done. The microparticles obtained were rather similar in shape (mostly round) and size (around 60μm) whatever the formulation but the obtained gel presented different elasticity (varying between 61 and 96Pa). An original equipment involving a granulo-morphometer coupled to a thermostated reactor was developed and validated to visualize in situ the microparticles during digestion. Although the initial particles were similar, their disintegration in simulated gastric media was totally different and characterized by two stages. An initial decrease in particle size more or less quick depending on the protein composition was followed by a stable phase characterized by the particle size and shape retention. At the end of gastric digestion, a significant amount of intact particles was still noticeable for each formulation. Nevertheless, the formulation containing a mix of casein and denatured whey presented the best bacterial survival (99%) and encapsulation rate (97%) in comparison with formulations containing either only casein or casein and native whey or casein in mixture with native and denatured whey proteins. This paper is part of a global project entitled “Structured dairy matrices to enhance probiotic efficiency”. The entire project will provide milk structured matrices allowing the stabilization and the vectorization of Lactobacillus rhamnosus GG (LGG). This project will consist of four main axes: milk constituent's interactions with LGG, stabilization process implementation, and structural and functional characterization of the matrices obtained. The scientific objective is to propose models connecting process parameters, matrix structure (from an atomic, molecular to a macro scale) and their functionality. This implies the in-depth study of interactions between milk components and probiotic strain. For this purpose, the use of genetically modified strain of LGG will allow the identification of biomolecules interacting with milk matrices. The industrial aims are to optimize and control the processes to suit the needs of industrial criterions: encapsulation rate, gastric resistance, intestinal release, storage in the final food…. •Milk protein matrices are good candidates to protect probiotics, especially LGG•Microparticle disintegration during digestion was followed with a granulo-morphometer•The optimum matrix consists of casein and denatured whey proteins